5‐Fluorouracil resistance mechanisms in colorectal cancer: From classical pathways to promising processes. Issue 9 (13th August 2020) - Blondy, Sabrina; David, Valentin; Verdier, Mireille; Mathonnet, Muriel; Perraud, Aurélie; Christou, Niki
Abstract: Colorectal cancer (CRC) is a public health problem. It is the third most common cancer in the world, with nearly 1.8 million new cases diagnosed in 2018. The only curative treatment is surgery, especially for early tumor stages. When there is locoregional or distant invasion, chemotherapy can be introduced, in particular 5‐fluorouracil (5‐FU). However, the disease can become tolerant to these pharmaceutical treatments: resistance emerges, leading to early tumor recurrence. Different mechanisms can explain this 5‐FU resistance. Some are disease‐specific, whereas others, such as drug efflux, are evolutionarily conserved. These mechanisms are numerous and complex and can occur simultaneously in cells exposed to 5‐FU. In this review, we construct a global outline of different mechanisms from disruption of 5‐FU‐metabolic enzymes and classic cellular processes (apoptosis, autophagy, glucose metabolism, oxidative stress, respiration, and cell cycle perturbation) to drug transporters and epithelial‐mesenchymal transition induction. Particular interest is directed to tumor microenvironment function as well as epigenetic alterations and miRNA dysregulation, which are the more promising processes that will be the subject of much research in the future. Abstract : Colorectal cancer is the third most common cancer worldwide. 5‐Fluorouracil (5‐FU), a synthetic fluorinated pyrimidine analog requiring intracellular conversion into active metabolites, is the main chemotherapy used when colorectal cancer is at an advanced stage or at high risk of recurrence. However, resistance to this treatment exists, explaining a low 5‐year survival rate. We review the main mechanisms of 5‐FU resistance, especially those linked to tumor microenvironment and genetic alterations.